UNVEIL THE DAY OF DISCOURSE ON THE USE OF TRADITIONAL BALINESE CLOTHING FOR ASN IN THE PROVINCIAL GOVERNMENT OF BALI - Suarmini, Desak Putu Andi; Suarka, I Nyoman; Sukiada, I Nyoman (E-Journal of Cultural Studies; Volume 12, Number 4, November 2019, 2019)
This study aims to uncover the form of power relations and the implications of the discourse on the use of traditional Balinese clothing for the State Civil Apparatus (ASN) in the Provincial Government of Bali. The rules on the use of traditional Balinese clothes for the ASN Bali Provincial Government are the implementation of the policy of the Governor of Bali Wayan Koster at the beginning of his leadership period and has been set forth in the Governor Regulation No. 79 of 2018 concerning the Day of the Use of Customary Bali Clothing. The study uses the scientific foundation of Cultural Studies with a qualitative approach. Two theories used in this research are the theory of power and knowledge relations and social practice theory. These two theories are collaboratively used to uncover the power relation forms and the implications of the discourse on the use of traditional Balinese clothes for ASN within the Provincial Government of Bali. The study revealed the form of power relations in the day-to-day discourse on the use of traditional Balinese clothes for ASN in the Provincial Government of Bali, namely governmentality in the form of regulations aimed at making the application of Balinese customary dress rules effective. Another form of power relation is the hegemonic ideology that is by utilizing the myths of Balinese traditional clothing and symbolic power relations using meaningful symbols. The results also revealed that the discourse on the use of Balinese traditional clothing for ASN in the Environment of the Provincial Government of Bali has implications for the representation of social classes marked by the desire of a group of ASN to differentiate themselves by adding accessories to the traditional clothes they wear. Another implication is consumerism among ASNs, where their desire engine is motivated to add custom clothing collections to the office beyond what they actually need. The application of traditional Balinese dress rules for the Bali Provincial Government ASN also gives rise to what is called cultural hybridization.  Keywords: discourse, Balinese traditional clothing, State Civil Apparatus